Formant Frequencies under Cognitive Load: Effects and Classification. (26th December 2010) - Yap Yap, Tet Fei Tet Fei; Epps Epps, Julien Julien; Ambikairajah Ambikairajah, Eliathamby Eliathamby; Choi Choi, Eric H. C. Eric H. C.
Abstract : Cognitive load measurement systems measure the mental demand experienced by human while performing a cognitive task, which is useful in monitoring and enhancing task performance. Various speech-based systems have been proposed for cognitive load classification, but the effect of cognitive load on the speech production system is still not well understood. In this work, we study formant frequencies under different load conditions and utilize formant frequency-based features for automatic cognitive load classification. We find that the slope, dispersion, and duration of vowel formant trajectories exhibit changes under different load conditions; slope and duration are found to be useful features in vowel-based classification. Additionally, 2-class and 3-class utterance-based classification results, evaluated on two different databases, show that the performance of frame-based formant features was comparable, if not better than, baseline MFCC features.